Potential Antimigraine Effects of Warfarin: An Exploration of Biological Mechanism with Survey of Patients - Nilsson, Benjamin; Back, Valentina; Wei, Ran; Plane, Frances; Jurasz, Paul; Bungard, Tammy J. (TH Open, 2019)
Case reports suggest a link between anticoagulant use and improved migraine symptoms, and a role for platelet-induced cerebral vasoconstriction in migraine pathobiology. Hence, we investigated the mechanism by which warfarin may affect migraine symptoms and whether there is a change in migraine symptomology in patients initiating oral anticoagulants, most commonly warfarin. The effects of warfarin on human platelet aggregation and secretion as well as platelet-induced rat cerebral artery vasoconstriction were studied. A survey of migraine and symptom change after starting or stopping oral anticoagulants was also conducted. Warfarin inhibited platelet aggregation and 5-hydroxytryptamine (5-HT) secretion in a concentration-dependent manner. Warfarin-inhibited platelet secretion products constricted middle cerebral arteries from male but not from female rats. For the survey, patient demographic information, migraine and medical history, and Migraine Disability Assessment Score (MIDAS) changes were collected. Out of 175 consenting, 40 respondents met the criteria for migraine and completed the survey. A total of 11 patients reported migraine symptom change, all coinciding with starting warfarin. Of those having symptom and MIDAS improvement, most were female with migraines with aura, whereas those worsening were male with fewer having migraine with aura. Of those reporting migraine symptom change with warfarin, female sex may be associated with improved MIDAS, and those experiencing an aura component are more likely to report a symptom change. Warfarin-mediated symptom improvement in females may occur due to inhibition of platelet 5-HT secretion and a lower sensitivity of female cerebral blood vessels to platelet-derived 5-HT-induced vasoconstriction.
Keywords: warfarin; migraine; platelets; serotonin; blood vessels